Síntese de nanopartículas de quitosana/PLA para liberação controlada de antibiótico no tratamento de mastite - Castro, Karine Cappuccio De (2017)
Bovine mastitis causes a serious impact on the dairy sector, causing serious damage, both due to the functional impairment of the mammary gland, with reduced milk production. In addition, it causes serious risks to public health, as the major species of bacterial pathogens that cause mastitis are produce toxin. In this context, nanotechnology is a very interesting alternative to overcome the limitations of conventional mastitis treatments, through the creation of nanostructured devices that are able to direct the antimicrobial to the surface of the glandular epithelium and into the affected tissue in order to potentiate the effect of the antibiotic under bacteria. The use of chitosan and Polylactic Acid (PLA) for this type of application is due to its numerous properties, especially biocompatibility and biodegradability. Thus this work was aimed at obtaining and characterization of nanoparticles for controlled release of gentamicin (GEN) through the emulsification - solvent evaporation. The nanoparticles were characterized by Scanning Electron Microscopy (SEM) coupled to a Dispersive Energy Detector (EDS), Infrared Spectroscopy with Fourier Transform (FTIR), Dynamic Light Scattering (DLS) and Zeta Potential measurements. In addition, the efficiency of encapsulation of gentamicin, the in vitro release of gentamicin using the dialysis method and the antimicrobial activity through the disc diffusion test and the determination of the Minimum Inhibition Concentration (MIC) by the successive microdilution method, using Staphylococcus aureus, were evaluated. DLS analyses showed an average nanoparticle size between 150 and 400 nm, varying with the composition of the formulation. The SEM analyzes correlated well with the DLS measurements, by this analysis it was also possible to observe the formation of agglomerates under certain conditions of synthesis. By FTIR analysis through the characteristic bands and the enlargement and/or increase of the bands intensification, confirmed the interaction between the components of the formulation, suggesting the formation of a core-shell nanoparticle, where the PLA would be in the nucleus and the chitosan in the shell. The study of zeta potential as a function of pH showed that the particles have positive surface charges, which is attractive for cell adhesion. The encapsulation efficiency varied from 66 to 75%, the 1:0.25 sample was the most successful in the encapsulation, suggesting that gentamicin, although hydrophilic, was also bound to PLA (hydrophobic). ESD analysis confirmed the presence of sulfur in all formulations containing gentamicin sulfate, which also confirmed the encapsulation of the antibiotic. The release assays showed that the highest concentration of gentamicin was released in the first 6 hours and that in the period from 24 to 96 hours that concentration remained in equilibrium. Finally, the antimicrobial assay is performed with the suspensions used in vitro release test showed the growth inhibition of Staphylococcus aureus main cause of bovine mastitis, and the MIC obtained for all samples was consistent with the literature.